2000
DOI: 10.1034/j.1399-3003.2000.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking status, disease duration, and educational level in females, are related to asthma school participation

Abstract: Limited data is available on those who do not want to attend an asthma school. Two hundred and forty-five asthmatics aged 18±65 yrs with an FEV1 >50% predicted who had been seen at our outpatient asthma clinic within the last 3 yrs were invited to participate in an asthma school. The patients were contacted by phone by a nurse, offered a 2 day asthma school without personal costs.Altogether 78% of those contacted answered positively. In a logistic regression analysis including sex, age, smoking status, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Unexpectedly they also found a decreased number of hospitalizations in the group of children with the highest cotinine level. 45 Among adults with asthma, current smokers have been found less likely to manage both acute and chronic asthma appropriately, 46,47 less likely to attend asthma education sessions, 5,[48][49][50] and overall less likely to use preventive healthcare services. 51 Our group also found that current smoking, less than HS education, and lower household income were predictors for lack of asthma knowledge and self-management skills.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly they also found a decreased number of hospitalizations in the group of children with the highest cotinine level. 45 Among adults with asthma, current smokers have been found less likely to manage both acute and chronic asthma appropriately, 46,47 less likely to attend asthma education sessions, 5,[48][49][50] and overall less likely to use preventive healthcare services. 51 Our group also found that current smoking, less than HS education, and lower household income were predictors for lack of asthma knowledge and self-management skills.…”
Section: Discussionmentioning
confidence: 99%
“…A community-based study in the UK found that smokers with chronic asthma were less likely than nonsmokers to use inhaled corticosteroids or peak flow meters, and to alter treatment during an exacerbation [47]. Smokers with asthma are less likely to attend asthma education programmes [49][50][51]. In an outpatient-based study of 125 asthmatics adults, only 4% of smokers, compared with 31% of former smokers and 65% of never-smokers, completed an asthma education programme [49].…”
Section: Patient Education and Self-managementmentioning
confidence: 99%